The Role of Brahmacharya (Tryaupstambh) in Health Promotion: A Systematic Review of Ayurvedic Principles and Contemporary Research (AYUSHDHARA, 2025)
Brahmacharya, one of the three fundamental pillars of Ayurveda (Tryaupstambh), is traditionally regarded as the disciplined practice of self-restraint, particularly in sexual behavior, to preserve Ojas, maintain Agni, and promote overall health. With the rising prevalence of lifestyle-related disorders, Brahmacharya has attracted renewed scientific interest. This systematic review analyzed classical Ayurvedic literature alongside modern experimental studies, clinical trials, and systematic reviews up to August 2025, sourced from PubMed, AYUSH Research Portal, Scopus, Web of Science, and authenticated classical texts. A total of 35 studies were included, revealing that Brahmacharya positively impacts hormonal balance, oxidative stress, cognitive function, psychological well-being, reproductive health, and metabolic parameters. Clinical trials demonstrated improvements in sperm quality, menstrual regularity, BMI, glucose tolerance, and mental health outcomes. However, the evidence is limited by heterogeneous study designs, small sample sizes, short durations, lack of standardized protocols, and insufficient mechanistic investigations. This review concludes that while Brahmacharya shows potential as a holistic preventive and therapeutic practice, further rigorous, large-scale randomized controlled trials and long-term studies are needed to establish standardized methodologies and validate its clinical efficacy.